Experiencing the landscape in antiquity - Cristilli, Armando 1972-; Gonfloni, Alessia; Stok, Fabio (BAR Publishing, 2020)
The book contains the results of the 1st International Conference on Classical Antiquities, held in Rome from 15th to 17th May 2019 at the ?Tor Vergata? University. This conference stimulated dialogue across different disciplines, from ancient history to medieval literature and archaeology, producing innovative research, original methodologies and comparative studies. The geographical area chosen was the ancient Mediterranean between the 6th century BC and the 7th century AD.0/0Questo libro contiene i risultati del 1° Convegno Internazionale di Antichità Classiche, svoltosi a Roma il 15/17 maggio 2019 presso il Dipartimento di Studi Letterari, Filosofici e di Storia dell?Arte dell?Università degli Studi ?Tor Vergata?. Pertanto, in linea con tale tradizione di studi, questa conferenza ha mirato a stimolare il dialogo tra diverse discipline, dalla storia antica alla letteratura medievale, all?archeologia. Così, la ricerca innovativa, le metodologie più originali e gli studi comparativi sono stati particolarmente presi in considerazione. L'area geografica prescelta è stata il Mediterraneo antico tra il VI sec. a.C. e il VII sec. d.C.
Keywords: Antike; Siedlungsarchäologie; Landschaftsentwicklung; Konferenzschrift -- 1st International Conference on Classical Antiquities -- 15.05.2019-17.05.2019 -- Rom